Environmental analysis of different construction techniques and maintenance activities for a typical local road. (20th January 2017) - Celauro, Clara; Corriere, Ferdinando; Guerrieri, Marco; Lo Casto, Barbara; Rizzo, Angela
Abstract: In this paper, considering the sever impact of road infrastructures on both the surrounding environment as well as on the consumption of locally available natural resources, different road construction techniques have been studied and compared, in order to be able to rank the best solution in terms of environmental sustainability. For the aims of this study, a Life Cycle Analysis has been carried out on a road infrastructure with the most representative geometrical characteristics among those widely used in Italy, in suburban areas, with the help of an appropriate software, the PaLATE. The environmental effects due to both the use of recycled materials, such as the Reclaimed Asphalt Pavement (RAP) from dismissing of damaged pavement layers, and the reuse of fine soil from excavation, traditionally sent to landfill, has been studied. The latter is possible thanks to lime stabilization of clayey soils, that allows to reduce the need of transport to the dump as well as the need for non-renewable natural resources for road subgrades and embankments. The results here obtained show how the use of RAP, can lead to a significant reduction in pollutant emissions and energy consumption compared to that due to pavements constructed with virgin material only. A similar observation can be made for fine soils stabilized (in situ) with lime: it is demonstrated that this technique is able not only to significantly improve the mechanical properties of useless soils that, otherwise, would be considered as a waste to be dumped but also to provide considerable environmental benefits. Finally, in order to identify a criterion for achieving lower generalized costs in the whole life cycle of a road, the different construction options have been estimated in terms of total direct costs, assessed as the sum of construction and maintenance costs. It has been verified that the use of sustainable construction techniques (RAP and lime stabilization of clayey soils) can lead to the reduction of total cost and thus allows allocating greater financial resources to perform an "ideal" maintenance plan. Graphical abstract: Highlights: Many road construction techniques and maintenance plans are analysed. An Life Cycle Assessment for many scenarios of a typical local road is carried out. Lime stabilized soils are examined and different percentage of RAP are considered. Construction, maintenance, and total costs are estimated.